The Internet of Things application on Student Assignee Smart Box using ESP32-Cam - Deosa Putra Caniago (Jurnal CoSciTech (Computer Science and Information Technology), 2022)
the development of Internet of Things technology, everything can be controlled over an unlimited distance using the internet network. Being a student is inseparable from project assignments that have deadlines for submission, problems that arise are sometimes the lecturers concerned are challenging to find, causing students to be delayed in submitting studies which affect student performance in the eyes of lecturers. In this case, an assignment recipient smart box system is created using the Wifi ESP32 Cam module and PIR Sensor which will monitor the collection of project assignments from students based on the Internet of Things, the system will send information in the form of photos to lecturers via Telegram Bot so that it can improve student performance in the eyes lecturer.